An Analysis Of Figurative Language In The Lyrics Let It Go Song By Idina Menzel - siti arin; Nur Azmi Rohimajaya; Riandi Riandi (Journal of English Education Studies, 2025)
This research analyzes the use of figurative language in the lyrics of the song “Let It Go” by Idina Menzel, which is widely known as a theme song of Disney’s “Frozen”. The study aims to identify and classify various types of figurative language, such as metaphor, simile, personification, hyperbole, idiom, alliteration, and symbolic expressions, and interpret their meanings using a qualitative descriptive approach. Drawing on Ferdinand de Saussure’s semiotic theory, the research decodes the song’s linguistic signs (signifier and signified) to explore how language shapes meaning, emotion, and imagery in the lyrics. The findings show that the lyrics are rich in figurative expressions that represent Queen Elsa’s inner transformation, emotional struggles, and the symbolism of freedom and empowerment. Hyperboles and personifications are used to enhance the imagery of Elsa’s magical powers, while similes and metaphors illustrate emotional depth and resilience. The study concludes that figurative language in “Let It Go” not only adds aesthetic value but also serves as a powerful medium to convey character development and thematic elements such as identity, self-acceptance, and liberation. This research highlights the importance of understanding figurative language in songs to grasp deeper meanings and emotional nuances.